Small Mammals of Tekai Tembeling Forest Reserve (TTFR), Jerantut, Pahang, Peninsular Malaysia - Abdullah, Nur Izzati; Khodri, Nur Fatin; Tajul Arifin, Nurul Atikah; Abdul Rahim, Muhammad Rizal; Razali, Siti Hajar Atiqah; Amat Darbis, Nurul Darsani; Md Nor, Shukor (Journal of Sustainable Natural Resources, 2021)
Despite the increasing numbers of hydro-dam worldwide, only a handful of studies evaluated their impacts on biodiversity especially terrestrial small mammals. This survey aimed to provide an updated checklist and diversity status of small mammals inhabiting the Tekai-Tembeling Forest Reserve (TTFR), an area that has been extensively logged for the next phase of construction of dam. To elucidate further the species assemblages and diversity of small mammals within TTFR, a comparison was made to a nearby forest, Ulu Jelai Forest Reserve (UJFR), which was also has been logged for the development of Telom Dam. 10 days survey conducted in March 2018 by using cage-trapping and mist-netting techniques, successfully recorded a total of 27 species (Shannon Index (H’) = 3.11) in TTFR and 23 species (H’=2.62) in UJFR. Most of these species in TTFR were bats (56 individuals representing 22 species), rodents (three species representing four individuals) and squirrels (two species representing three individuals). Insectivorous bat species, Narrow-winged Pipistrelle (Pipistrellus cf. stenopterus), are the most abundance in TTFR mainly because insectivorous bats behavior that forage understory in a lowland forest and some of these bats is known to forage in groups. Results from this study indicated that richness and diversity of small mammal’s species assemblages appear to decline in TTFR at which this can be associated to less sampling approaches due to the seasonal impact (rainy season) and habitat disturbance or habitat changes resulted from extensive logging activity. A good mitigation measures should be conducted immediately to prevent elimination species at the study area.